2017
DOI: 10.1002/slct.201702041
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Nanoclay‐Reinforced Trifunctional “Bioresin‐Modified” Epoxy Blends Enhanced with Mechanical and Thermal Properties

Abstract: Epoxy/TEIA clay nanocomoposite was synthesized from renewable resource based itaconic acid trifunctional bioresin (TEIA) reinforced with Cloisite 93 A nanoclay (C93 A), which was further cured with an anhydride curing agent and 2‐methylimidazole as a catalyst. From the mechanical strength it was observed the tensile strength of virgin epoxy 42.94 MPa enhanced to 70.26 MPa with the incorporation of 2.5 wt% C93 A. Differential scanning calorimetry, thermal analysis, and dynamic mechanical analysis demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 56 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…The second weight loss step, which is started at about 400 °C and ended at 700 °C (about 5%), may be related to the water molecules which are located between the layers of bentonite. TGA analysis of polyacrylamide‐polystyrene/bentonite (Figure ) shows about 70% weight loss between 100 °C and 700 °C which is related to desorption of water molecules located inside the layers of nanocomposite, external surface of nanocomposite and degradation of polymer chains that are located between the layers of bentonite . Therefore, it can be concluded that polymer chains are successfully loaded on the surfaces of bentonite.…”
Section: Resultsmentioning
confidence: 97%
“…The second weight loss step, which is started at about 400 °C and ended at 700 °C (about 5%), may be related to the water molecules which are located between the layers of bentonite. TGA analysis of polyacrylamide‐polystyrene/bentonite (Figure ) shows about 70% weight loss between 100 °C and 700 °C which is related to desorption of water molecules located inside the layers of nanocomposite, external surface of nanocomposite and degradation of polymer chains that are located between the layers of bentonite . Therefore, it can be concluded that polymer chains are successfully loaded on the surfaces of bentonite.…”
Section: Resultsmentioning
confidence: 97%